Mogamulizumab combined with extracorporeal photopheresis as a novel therapy in erythrodermic cutaneous T-cell lymphoma - Ninosu, Nadia Nicole; Melchers, Susanne; Kappenstein, Max; Booken, Nina; Hansen, Inga; Blanchard, Maël; Guenova, Emmanuella; Assaf, Chalid; Goerdt, Sergij; Nicolay, Jan Peter (Cancers, 2024)
Background: Primary cutaneous T-cell lymphomas (CTCLs) are rare lymphoproliferative malignancies characterized by significant morbidity and mortality in advanced disease stages. As curative approaches apart from allogeneic stem cell transplantation are lacking, establishing new treatment options, especially combination therapies, is crucial. Methods: This retrospective study included 11 patients with SS or MF receiving therapy with mogamulizumab in combination with ECP from four European expert centers. The response rates in the skin and blood as well as treatment use and adverse events (AE) were described. Results: 8/11 patients (73%) showed an overall response (OR) in the skin. The mean mSWAT decreased from 98.2 ± 40.8 to 34.6 ± 23.8. The overall response rate (ORR) in the blood was 64% with two complete responses. During combination therapy, the mean number of Sézary cells decreased from 3365.3 × 106/L before treatment to 1268.6 × 106/L. The mean minimum known period without progress was 7.2 months in the skin and 7.6 months in the blood. The most common AEs were mogamulizumab-associated rash (MAR) (45.5%), anemia (27.3%), lymphocytopenia (27.8%), and infusion related reaction (16.7%). No AE led to treatment discontinuation. Conclusions: Our study presents the combination of mogamulizumab and ECP as an effective therapy in the blood and skin in CTCL with good tolerability, similar to mogamulizumab monotherapy.
Veröffentlicht: 27. Dezember 2023
Gesehen am 07.05.2024